Triassic floras of antarctica: Plant diversity and distribution in high paleolatitude communities - Escapa, Ignacio Hernán; Taylor, Edith L.; Cúneo, Néstor Rubén; Bomfleur, Benjamin; Bergene, Bergene; Serbet, Rudolph; Taylor, Thomas N. (PALAIOS)
Continental Triassic sequences in Antarctica are among the most continuous and best represented in Gondwana. Triassic fossil plants have been collected sporadically from Antarctica since the beginning of the twentieth century, but our knowledge of the vegetation during this time has dramatically increased during the last three decades. Here we review the fossil record of Triassic plants as representatives of natural groups from sites along the Transantarctic Mountains, using the fossils as evidence for successive vegetational changes through the Triassic, taking into account that these plant communities were living under particular high-latitude (706 or higher) paleoclimatological conditions, including a polar light regime. Even though our knowledge of the Triassic floras of Antarctica is still incomplete, this survey shows that these floras were remarkably diverse. Lycopsids, equisetaleans, ferns, seed ferns, ginkgoaleans, and conifers were major components of the landscape in Antarctica during this time. The diversity of gymnosperms is exceptional, with almost every major clade of seed plants present, despite the high paleolatitude; however, each clade is often represented by only one or a few genera. The occurrence of permineralized peat, along with compression-impression floras, has increased our knowledge of the morphology, reproductive biology, and evolution of many of the plants in these floras. In general, floral changes in Antarctica during the Triassic can be recognized elsewhere in Gondwana, especially in South America, although a strict correlation based on macrofossils is still not possible. Thus, this contribution represents the first attempt to bring together information on Triassic floras from continental Antarctica (excluding the Antarctic Peninsula) within a biostratigraphic framework and thereby to compare these floras with those from lower latitudes. Copyright © 2011, SEPM (Society for Sedimentary Geology. Fil: Escapa, Ignacio Hernán. Consejo Nacional de Investigaciones Científicas y ...